0344 20 years (1989–2008) of direct costs associated with falls from height among union carpenters, Washington State, USA. (23rd June 2014) - Lipscomb, Hester; Schoenfisch, Ashley; Cameron, Wilfrid; Kucera, Kristen; Adams, Darrin; Silverstein, Barbara
Abstract : Objectives: To examine trends in workers' compensation payments for falls from height (FFH) among a large cohort of carpenters over a 20-year period (1989–2008). Cost data provide an important metric reflecting frequency of falls and severity of associated injuries. Method: Using combined administrative data we evaluated workers' compensation (WC) payments associated with FFH among a large (n = 24 830) 20-year cohort (1989–2008) of union carpenters in Washington State. Mean payments, costs rates and adjusted rate ratios based on hours worked were calculated using negative binomial regression to evaluate cost patterns based on age, union tenure, type of carpentry work and calendar time after adjusting and discounting to 2011 dollar values. Results: FFH accounted for $66.6 million in WC payments (a burden of $0.35 per hour worked) over the 20-year period. FFH were responsible for 5.5% of injuries but 15.1% of costs. Marked cost declines were observed over time, but not in a monotonic fashion. Reductions were more pronounced for indemnity than for medical care. Mean costs per fall were unchanged in the latter years of observation from those observed 1995–1996. Individuals performing millwrighting or drywall installation had cost rates over twice as high as commercial construction. Mean costs were 2.3 times greater among carpenters over 50 than those under 30, but their cost rates were only modestly higher. Conclusions: Progress has been made in reducing direct costs associated with FFH in this cohort particularly though 1996, but primary gains reflect the reduction in frequency while FFH that occur remain serious.